Preventing Children From Developing Dyslexia: A Premature Writing Hypothesis. Issue 3 (June 2022) - Mather, David S.
It has been argued that dyslexia may develop in strongly left eye dominant children through learning to write using ipsilateral, right hemisphere motor pathways. New light on this theory has been cast by recent findings of atypical enhanced corpus callosum white matter in children with dyslexia, reflecting right to left hemisphere communication that is resistant to intensive remedial reading intervention. Enhanced corpus callosum white matter is consistent with uninhibited right to left hemisphere ipsilateral mirror-motor innervation, manifested as frequent mirror-letter writing errors in children with dyslexia. Delaying writing instruction until 7–8 years of age may prevent these errors and as well as the development of dyslexia. During the 7–8-year age period, visual-proprioceptive integration enables a child to mentally map whole word visual images onto kinesthetic/proprioceptive letter engrams (memory representations). Hypothetically, this process is facilitated by anterior commissure activity involving interhemispheric transfer of ipsilateral mirror-to-non mirror-motor movement. This postulate, involving delayed writing instruction pending further maturation, also receives indirect support from the remarkable proficiency leap among second graders reading Hebrew as Hebrew involves a leftward orthography in which ipsilateral right to left hemisphere innervation is uninhibited. Additionally, and more directly, normal reading comprehension for learning English among children with agenesis of the corpus callosum suggests that letter-sound decoding is not the sole route to proficient reading comprehension. In this paper, I make recommendations for obtaining empirical evidence of premature writing as a cause of dyslexia.